Mechanism of action of the bile acid receptor TGR5 in obesity - Weijun Lun; Qihao Yan; Xinghua Guo; Minchuan Zhou; Yan Bai; Jincan He; Hua Cao; Qishi Che; Jiao Guo; Zhengquan Su (Elsevier, 2024)
G protein-coupled receptors (GPCRs) are a large family of membrane protein receptors, and Takeda G protein-coupled receptor 5 (TGR5) is a member of this family. As a membrane receptor, TGR5 is widely distributed in different parts of the human body and plays a vital role in regulating metabolism, including the processes of energy consumption, weight loss and blood glucose homeostasis. Recent studies have shown that TGR5 plays an important role in glucose and lipid metabolism disorders such as fatty liver, obesity and diabetes. With the global obesity situation becoming more and more serious, a comprehensive explanation of the mechanism of TGR5 and filling the gaps in knowledge concerning clinical ligand drugs are urgently needed. In this review, we mainly explain the anti-obesity mechanism of TGR5 to promote the further study of this target, and show the electron microscope structure of TGR5 and review recent studies on TGR5 ligands to illustrate the specific binding between TGR5 receptor binding sites and ligands, which can effectively provide new ideas for ligand research and promote drug research.